Sosialisasi Pengetahuan Jamur Akar Putih pada Tanaman Karet kepada Masyarakat Petani Karet di Banyuasin III, Sumatera Selatan - Stenia Ruski Yusticia; Astri Febrianni; Rizky Randal Cameron; Rosita Rosita; Siti Rakhmi Afriani (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
White root disease is a major disease threatening the productivity of rubber plants. The community’s knowledge about White root disease is still limited, especially in recognizing early symptoms and its impact on rubber plants. Therefore, this community service activity aims to socialize knowledge about White root disease to the rubber plantation community in Banyuasin III, South Sumatra. This activity involves a series of counseling and interactive discussions about White root disease, including the introduction of symptoms, impacts on plants and the environment, and the importance of early detection. In addition, this activity also involves field demonstrations on how to identify White root disease symptoms in rubber plants. The results of this activity show an increase in community knowledge and awareness about White root disease. The community has become more capable of recognizing the early symptoms of White root disease and understanding the importance of early detection to prevent further spread. This activity contributes positively to the efforts of sustainable rubber plant management in Banyuasin III, South Sumatra.